THE PADANG ADMINISTRATION’S POLICY IN OVERCOMING AND DEVELOPING STREET CHILDREN - Frinaldi, Aldri; Putri, Nora Eka; Fitria, Helen (Humanus, 2015)
This study aims to analyze policy of Padang city administration in overcoming and developing street children. This qualitative descriptive research is located in the city of Padang, West Sumatra Province, Indonesia. The findings of this study indicate that street children activities around Padang’s Bagindo Azis Chan Street lasted on average six to twelve hours per day. The street children sell brooms, clean the windshield during rainy days, clean windshield using feather dusters, and sing. Most of the street children are no longer in school. Those who do not live with their parents tend to drop out of school. The average street children in the area confirm to have families with permanent residence in Padang area, but not all of them settle down with their family. The Padang city admnistration have trained and provided capital assistance for street children and their parents but is not yet sustainable while the funding can not afford to start adequate business.